PENGARUH LINGKUNGAN KOMPOSIT SERAT SABUT KELAPA UNTUK APLIKASI BALING-BALING KINCIR ANGIN - Bakri, Bakri; Chandrabakty, Sri; Alfriansyah, Alfriansyah; Tahir, Mohammad (Jurnal MEKANIKAL, 2014)
Abstract: Environmetal Effect of Tensile, Modulus and Shear Strength of Coir Fibre Composite. The aim of this research is to know the environmetal effect of tensile, modulus and shear strength of coir fibre composite. In this research, coir is used as reinforcement and matrix uses epoxy resin. Coir is soaked in water with 5% NaOH during 24 hours. Composite is moulded with 17 % fibre volume fraction and 83% matrix volume fraction. Then, the tensile specimen used ASTM D638-02 and shear specimen used ASTM D5379 standard. Universal Testing Machine is used to test of these spesimens. The specimens of tensile and shear include without and with treatment to environmental influence during 10, 20, and 30 days. The result shows that tensile strength, modulus and shear strength of specimen treatment during 10, 20, 30 days are not significantly decreased from specimen without treatment. This result can be used as recommadation for material of wind blade for the future. Keywords: composites, coir fiber, shear strength, tensile strength